Preparation method of co-fired integrated inductor and inductor
By forming a uniform Al2O3 cladding layer on the surface of the inductive alloy powder, and combining the local liquid-solid phase reaction of MoO3 with Al2O3 and ferro-based alloy powder, the problem of low reliability of the inductive coating is solved, and the preparation of copper-iron co-fired inductor with low loss and high current resistance is achieved.
Patent Information
- Application Number
- CN202411872388.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The existing inductor has low reliability at high temperatures, resulting in high losses, poor performance withstand high currents, and high-voltage molding is prone to damage to the insulating layer.
A uniform Al2O3 cladding layer was formed on the surface of the alloy powder by atomic deposition technology, and an insulating and coupling layer was formed by local liquid-solid phase reaction between MoO3 and Al2O3 and ferro-based alloy powder. Inductors were prepared by sintering at high temperatures in combination with copper-iron co-fired technology.
It improves the reliability of the inductor coating, reduces losses, enhances high current resistance, and avoids the damage to the insulating layer caused by high-voltage molding.
Smart Images

Figure CN119724895A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inductor preparation, and in particular to a preparation method of a co-fired integrated inductor and the inductor. Background Art
[0002] The statements in this section merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] The plastic encapsulation materials used in traditional molded inductors contain organic matter. Inorganic matter ages and fails at high temperatures, resulting in low reliability of product characteristics and insufficient product strength, and magnets are easy to fall off. The use of copper-iron co-firing technology can effectively avoid such problems. Compared with low-temperature solidified alloy powder, alloy powder sintered at high temperature has the advantages of high magnetic permeability, high saturation magnetic induction intensity, high thermal conductivity and ultra-low core loss. At present, the molded alloy powder sintered inductors used in the traditional method mostly use high-temperature resistant silicone or water glass as a curing agent for sintering annealing. This method has the following disadvantages: high temperature will have an irreversible effect on the reliability of modified silicone. In addition, water glass needs to be prepared and used immediately, which is not conducive to large-scale granulation powder reserve production. High-pressure pressing will destroy the brittle inorganic coating layer, and the coating layer will also affect the insulation effect between the powder particles. The reduction in surface resistance will cause an increase in the loss of the sintered inductor. For compression molding, in order to obtain a higher density, a pressure of more than 2000Mpa is often required to press the green body. Excessive pressure will cause serious deformation of the powder particles, and the insulating coating will be squeezed, deformed or even ruptured, causing the loss of the magnetic powder core to increase irreversibly.
[0004] Therefore, how to make the prepared inductor have low loss, withstand large current and have stable coating has become a technical problem that needs to be urgently solved in the existing technology. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a co-fired integrated inductor and an inductor, which can effectively reduce the total loss of the terminal product, improve the conversion efficiency, and solve the problem of low reliability of the coating layer.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A first aspect of the present invention provides a method for preparing a co-fired inductor, comprising the following steps:
[0008] The alloy powder is sequentially subjected to atomic deposition, double-layer coating and granulation processes to prepare inductor granulated powder;
[0009] Granulate and press the inductor granulated powder into a shape;
[0010] Sintering the formed inductor;
[0011] After the sintered inductor is subjected to rust-proofing work, the inductor preparation is completed.
[0012] Furthermore, the alloy powder is atomized iron-based alloy powder, and the iron-based alloy powder is composed of one or more of FeSiCr, FeSiAl, FeSi, and FeNi alloy powders.
[0013] Furthermore, in the double-layer coating process, the preparation process of the first coating layer of the alloy powder is as follows:
[0014] A 1nm to 3nm Al2O3 layer is grown in situ on the surface of the alloy powder using a fluidized bed atomic deposition device.
[0015] Furthermore, in the double-layer coating process, the preparation process of the second coating layer of the alloy powder is as follows:
[0016] The powder after atomic deposition is mixed with methyl cellulose, sub-nano Mo2O3 and sub-nano titanium dioxide, and anhydrous ethanol is added to the above solid phases for stirring until the ethanol in the powder evaporates, and then air-dried.
[0017] Furthermore, the mass fractions of the powder after atomic deposition, methyl cellulose, subnano Mo2O3 and subnano titanium dioxide are respectively: 95wt% of the powder after atomic deposition, 1.0wt% of methyl cellulose, 2.5wt% of subnano Mo2O3 and 1.5wt% of subnano titanium dioxide.
[0018] Furthermore, after pressing, the molded product was debonded at 450°C for 1 h in a N2 atmosphere to remove the organic phase in the green body.
[0019] Furthermore, the formed inductor is placed in an atmosphere sintering furnace for sintering, and the atmosphere is a nitrogen and hydrogen atmosphere.
[0020] Furthermore, during the sintering process, the sintering temperature is between 750 and 800°C, the gas flow ratio is N2:H2=3:1, and the sintering time is 1h.
[0021] Furthermore, the specific steps of the rust prevention work are: spraying the sintered inductor with rust prevention, and then folding the legs of the sprayed integrated inductor.
[0022] A second aspect of the present invention provides an inductor, which is prepared by the method for preparing the co-fired inductor described in the first aspect.
[0023] One or more of the above technical solutions have the following beneficial effects:
[0024] The invention discloses a preparation method of a co-fired integrated inductor and an inductor. The inductor prepared by using a traditional molded integrated inductor has a high loss, while the inductor prepared by using a copper-iron co-fired technology can not only withstand large currents but also has extremely low losses.
[0025] In the existing copper-iron co-firing process, high temperature is not conducive to the reliability and stability of the current coating layer. On the one hand, the use of high-temperature resistant modified silicone resin as a binder will have a certain aging risk; on the other hand, although the inorganic water glass used as a binder to prepare the granulated powder has good high-temperature stability, the carbon dioxide in the atmosphere will react with the water glass and carbonize, and the prepared powder needs to be prepared and used immediately, which is not conducive to continuous production. The present invention uses atomic deposition technology to form a uniform coating layer on the surface of the alloy powder, and forms an insulating and bonding layer through a local liquid-solid phase reaction between MoO3 and Al2O3 and the iron-based alloy powder. It has high strength and reliability, solves the problem of low reliability of the coating layer in the copper-iron co-firing technology, and can be sintered under high temperature (750-800℃) conditions to prepare high-density iron-based alloy powder inductors.
[0026] In addition, the grain orientation of the chip inductor caused by unidirectional high voltage is serious, and it is difficult to completely eliminate the huge internal stress. The insulation layer is very easy to be damaged, which is not conducive to reducing the loss of the inductor. The present invention solves the problem of lattice deformation and insulation layer damage caused by high voltage through local solid phase sintering technology, greatly reduces the inductor loss, and can avoid the adverse effects of high voltage.
[0027] Advantages of additional aspects of the present invention will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0029] Figure 1 This is a schematic diagram of sintering high current inductor granulated powder in Example 1 of the present invention;
[0030] Figure 2 This is a front schematic diagram of a sintered high current inductor structure in Embodiment 1 of the present invention;
[0031] Figure 3 It is a schematic diagram of the back side of the sintered high current inductor structure in the first embodiment of the present invention. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "include" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or their combinations;
[0034] Embodiment 1:
[0035] Embodiment 1 of the present invention provides a method for preparing a co-fired integrated inductor. At present, the inductor loss prepared by the traditional molded integrated inductor is relatively high (1.3W / cm3@50mT&100kHz), while the inductor prepared by the copper-iron co-firing technology can not only withstand large currents, but also has extremely low losses (0.13W / cm3@50mT&100kHz). In the existing copper-iron co-firing process, high temperature is not conducive to the reliable stability of the current coating layer. On the one hand, the use of high-temperature resistant modified silicone resin as a binder will have a certain aging risk; on the other hand, the use of inorganic water glass as a binder to prepare granulated powder, although it has good high-temperature stability, the carbon dioxide in the atmosphere will react with the water glass and carbonize, and the prepared powder needs to be prepared and used immediately, which is not conducive to continuous production.
[0036] The present invention utilizes atomic deposition technology to form a uniform coating layer on the surface of alloy powder, and forms an insulating and bonding layer through local liquid-solid phase reaction of MoO3, Al2O3 and iron-based alloy powder. The layer has high strength and reliability, solves the problem of low reliability of the coating layer in the copper-iron co-firing technology, and can be sintered under high temperature (750-800°C) conditions to prepare high-density iron-based alloy powder inductors.
[0037] The specific steps include:
[0038] Step 1: Prepare inductor granulated powder by subjecting the alloy powder to atomic deposition, double-layer coating and granulation processes in sequence.
[0039] A layer of aluminum oxide insulation is grown in situ on the surface of alloy magnetic powder using atomic deposition technology. The aluminum oxide layer has high density and high resistance, which is mainly used to increase the surface resistance of the powder and reduce eddy current loss. The second coating layer is a two-phase sintering bonding layer, which is used to form a connection between powder materials. Sub-nanometer molybdenum oxide and titanium dioxide are used as sintering aids to achieve localized liquid phase sintering of iron-based alloy powder, MoO3 and TiO2.
[0040] Step 1.1: preparing alloy powder. The alloy powder is selected from gas-atomized iron-based alloy powder, and the iron-based alloy powder is composed of one or more of FeSiCr, FeSiAl, FeSi, and FeNi alloy powders.
[0041] Step 1.2: Prepare the first coating layer. In the double-layer coating process, the preparation process of the first coating layer of the alloy powder is as follows:
[0042] A fluidized bed atomic deposition device is used to in-situ grow a 1nm to 3nm Al2O3 layer on the surface of the alloy powder. The first precursor Al(CH3)3 (trimethylaluminum, TMA) and the second precursor H2O or oxygen plasma are used for atomic layer deposition based on the principle of Al2O3 coating.
[0043] Step 1.3: Prepare the second coating layer. In the double-layer coating process, the preparation process of the second coating layer of the alloy powder is as follows:
[0044] The powder after atomic deposition is mixed with methyl cellulose, sub-nano Mo2O3 and sub-nano titanium dioxide, and anhydrous ethanol is added to the above solid phases for stirring until the ethanol in the powder evaporates, and then air-dried.
[0045] Preferably, 7 wt % of anhydrous ethanol is added to the above solid phase and stirred for 40 minutes until the ethanol in the powder evaporates, and then air-dried for 25 minutes.
[0046] Preferably, the mass fractions of the powder after atomic deposition, methyl cellulose, subnano Mo2O3 and subnano titanium dioxide are: 95wt% of the powder after atomic deposition, 1.0wt% of methyl cellulose, 2.5wt% of subnano Mo2O3 and 1.5wt% of subnano titanium dioxide.
[0047] Step 2: Granulate and press the inductor granulated powder into shape.
[0048] Step 2.1: Granulation: The air-dried powder is extruded and granulated, and the mesh size of the sieve is 50 mesh.
[0049] Step 2.2: Pressing and molding. Put the "J"-shaped copper sheet into the molding press cavity, fill it with powder and press it with a pressure of 100Mpa and hold the pressure for 5s.
[0050] This embodiment uses low-pressure molding technology to press the integrated inductor ligand (100Mpa). Because excessive pressure will cause serious deformation of the powder particles, the insulating coating layer will be squeezed, deformed or even ruptured, causing the magnetic powder core loss to increase irreversibly.
[0051] Step 2.3: Debinding: After pressing and molding, debinding was performed at 450°C for 1 h in a N2 atmosphere to remove the organic phase in the green body.
[0052] Step 3: Sinter the formed inductor.
[0053] Sintering mechanism: Figure 1 As shown in the figure, the interfacial reaction between the MoO3 melt and the iron-based alloy powder at high temperature reduces the surface energy, so that the MoO3 melt can fully wet the alloy magnetic powder, and the local interfacial reaction also helps to obtain a higher two-phase (liquid-solid) bonding force. At the same time, TiO2 and deposited Al2O3 have good lattice matching, and the progressive oxygen release of TiO2 can ensure the controllable oxidation of the iron-based powder, which itself becomes ferromagnetic under oxygen-deficient conditions, thereby reducing the magnetic dilution effect. Furthermore, the iron-based powder particles are effectively isolated by the deposited Al2O3 insulating layer, thereby reducing eddy current losses. Among them, the local interfacial reaction is the interfacial reaction between powder particles.
[0054] In a specific implementation, the formed inductor is placed in an atmosphere sintering furnace for sintering, and the atmosphere is a nitrogen and hydrogen atmosphere.
[0055] Preferably, during the sintering process, the sintering temperature is between 750 and 800° C., the gas flow ratio is N2:H2=3:1, and the sintering time is 1 hour.
[0056] Preferably, the sintering temperature is 780°C.
[0057] Step 4: After the sintered inductor is rust-proofed, the inductor preparation is completed. Figure 2 and Figure 3 shown.
[0058] The specific steps of the rust prevention work are: spray the sintered inductor with rust prevention, and then fold the legs of the sprayed integrated inductor.
[0059] By adopting the above steps, a high-reliability, low-loss, high-performance copper-iron co-fired inductor can be prepared. In order to prove the effectiveness of the method of this embodiment, a series of experiments were conducted according to the parameters in Table 1 for comparison.
[0060] The size of the prepared one-piece molded inductor is 10.0*7.0*6.0 mm. The comparative example is conventional molding, the molding pressure is 600 MPa, and the curing is baked at 180° C. The embodiment is an inductor prepared by copper-iron co-firing technology.
[0061] Table 1: Performance parameters of inductors prepared in comparative examples and examples
[0062]
[0063] From Table 1, we can see that the co-fired inductor prepared by sintering technology has lower loss and excellent DC bias capability. In addition, although the molded inductor prepared by alloy powder has excellent DC bias capability, it has high loss and low initial magnetic permeability and cannot meet the high inductance requirements of chip inductors.
[0064] The copper-iron co-firing technology adopted by the present invention can effectively reduce the total loss of the terminal product and improve the conversion efficiency; the miniaturization of the product can reduce the size of the terminal product. In addition, the copper-iron co-firing inductor has a higher density and better thermal conductivity, which is beneficial to the heat dissipation of the chip inductor.
[0065] Embodiment 2:
[0066] A second embodiment of the present invention provides an inductor, which is prepared by the method for preparing the co-fired inductor described in the first embodiment.
[0067] The steps involved in the above embodiment 2 correspond to those in the method embodiment 1. For the specific implementation method, please refer to the relevant description part of the embodiment 1.
[0068] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing a co-fired inductor, characterized in that: The following steps are involved: The alloy powder is sequentially subjected to atomic deposition, double-layer coating and granulation processes to prepare inductor granulated powder; Granulate and press the inductor granulated powder into shapes; Sintering the formed inductor; After the sintered inductor is subjected to rust-proofing work, the inductor preparation is completed.
2. The method for preparing a co-fired inductor according to claim 1, characterized in that: The alloy powder is atomized iron-based alloy powder, and the iron-based alloy powder is composed of one or more of FeSiCr, FeSiAl, FeSi, and FeNi alloy powders.
3. The method for preparing a co-fired inductor according to claim 1, characterized in that: In the double-layer coating process, the preparation process of the first coating layer of the alloy powder is as follows: A 1nm to 3nm Al2O3 layer is grown in situ on the surface of the alloy powder using a fluidized bed atomic deposition device.
4. The method for preparing a co-fired inductor according to claim 1, characterized in that: In the double-layer coating process, the preparation process of the second coating layer of the alloy powder is as follows: The powder after atomic deposition is mixed with methyl cellulose, sub-nano Mo2O3 and sub-nano titanium dioxide, and anhydrous ethanol is added for stirring until the ethanol in the powder evaporates, and then air-dried.
5. The method for preparing a co-fired inductor according to claim 4, characterized in that: The mass fractions of the powder after atomic deposition, methyl cellulose, subnano Mo2O3 and subnano titanium dioxide are respectively: 95wt% of the powder after atomic deposition, 1.0wt% of methyl cellulose, 2.5wt% of subnano Mo2O3 and 1.5wt% of subnano titanium dioxide.
6. The method for preparing a co-fired inductor according to claim 1, characterized in that: After pressing, the organic phase in the green body was removed by debinding at 450 °C in a N2 atmosphere for 1 h.
7. The method for preparing a co-fired inductor according to claim 1, characterized in that: The formed inductor is placed in an atmosphere sintering furnace for sintering in a nitrogen and hydrogen atmosphere.
8. The method for preparing a co-fired inductor according to claim 7, characterized in that: During the sintering process, the sintering temperature is between 750 and 800°C, the gas flow ratio is N2:H2=3:1, and the sintering time is 1h.
9. The method for preparing a co-fired inductor according to claim 1, characterized in that: The specific steps of the rust prevention work are: spray the sintered inductor with rust prevention, and then fold the legs of the sprayed integrated inductor.
10. An inductor, characterized in that: The inductor is prepared by the method for preparing a co-fired inductor according to any one of claims 1 to 9.
Citation Information
Cited By
Integrally-formed inductor and preparation method and application thereof
CN120453029A
Co-fired integrally-formed inductor and preparation method and application thereof
CN120581360A